Pengaruh Tanah Liat Terhadap Penyerapan Air Hujan Pada Tanaman - Lola Sri Wahyuni Halawa; Dilva Dwi Wulan Halawa; Julvan Ndruru (CV. SINAR HOWUHOWU, 2026)
This study aimed to explore the effect of clay soil on rainwater absorption and plant growth. Using a factorial experimental design, the study compared the ability of clay soil and sandy soil to retain water and support the growth of rice, maize, and vegetable crops. The results showed that clay soil had a higher water retention capacity, with an average soil moisture content of 30% after simulated rainfall, compared to 15% in sandy soil. Plants grown in clay soil exhibited better growth performance, with an average height of 45 cm, 12 leaves per plant, and a dry biomass of 40 g, whereas plants grown in sandy soil reached only 30 cm in height, produced 7 leaves, and had a dry biomass of 25 g. These findings highlight the importance of soil type selection in sustainable agricultural practices, with clay soil serving as a more efficient growing medium for enhancing water availability and promoting plant growth.